2014
DOI: 10.1111/pcn.12146
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression, examination‐related stressors, and sense of coherence: The ronin‐sei study

Abstract: Aims:In the Japanese education system, students who fail university entrance exam often go to special preparatory schools to prepare for the following year's exam. These students are called ronin-sei. The purpose of this study was to clarify: (i) depression and somatic complaints in ronin-sei; and (ii) the association between depression, examination-related stressors, and sense of coherence (SOC).Methods: A total of 914 ronin-sei from two preparatory schools were asked to answer a self-rating questionnaire. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…These findings are consistent with the study conducted in Japan. 30 The study conducted by Krishnakumar P and Geeta MG found a significant association between examination failures and depression. 25…”
Section: Discussionmentioning
confidence: 96%
“…These findings are consistent with the study conducted in Japan. 30 The study conducted by Krishnakumar P and Geeta MG found a significant association between examination failures and depression. 25…”
Section: Discussionmentioning
confidence: 96%
“…In Japan, if students are not accepted by universities, they often go to a private 'cram' school to study for another year and retake the university entrance exams the following year. These students are called "Ronin" [34,35]. Previous research found that "Ronin" students were sleep deprived, relatively depressed, and had various somatic complaints during the period before they retake the tests and successfully pass the exam [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…e standardization of entrance exams for both high schools and universities-coupled with a stringent national curriculum for Japanese schools nationwide-reiterates a perception that the Japanese educational system does not accommodate individual learning needs that each student may possess [41,42]. With only 33% of students passing the entrance exam, leaving 100,000 students who are not admitted to universities [43], the pressures to be academically successful negatively impact the mental health of both high school and university students.…”
Section: Discussionmentioning
confidence: 99%